PEMBELAJARAN BERDIFERENSIASI BERDASARKAN KERAGAMAN DAN KEUNIKAN SISWA SEKOLAH DASAR - Fitriyah, Fitriyah; Bisri, Moh (Universitas Negeri Surabaya, 2023)
Differentiated learning is learning that accommodates student learning needs. The teacher provides facilities to students according to their needs, because each student has different characteristics, so they cannot be given the same treatment. The purpose of this article is to provide a deeper understanding of differentiated learning and how it is applied in the classroom. This research uses literature study or library research. Literature study is the activity of collecting materials related to research originating from books, scientific journals, literatures and other publications that are worthy of being used as sources for research that will be examined by the author, by describing and describing the data. through several expert opinions. The results of conceptual research reveal that there are differentiated learning objectives, namely to coordinate learning by paying attention to learning interests, learning readiness and learning preferences, helping all students in learning so that learning objectives can be achieved by all students; improve student motivation and learning outcomes; establish a harmonious relationship between teachers and students so that students can be more enthusiastic in learning, help students become independent students so that they become individuals who are accustomed and also have an attitude of respect for diversity, increase teacher satisfaction because there is a sense of being challenged to want to develop their teaching abilities so that teachers will become more creative. It can be concluded that differentiated learning provides opportunities for students to be able to learn naturally and efficiently with teachers who are able to collaborate on the required methods and approaches.